Synthesis of novel crosslinked sulfonatod poly(ether sulfone)s using bisazide and their properties for fuel cell application - Oh, Young-Seok; Lee, Hye-Jin; Yoo, Minji; Kim, Hyoung-Juhn; Han, Jonghee; Kim, Tae-Hyun (ELSEVIER, 2008)
Novel crosslinked sulfonated poly(ether sulfone)s (PESs) were prepared by thermal irradiation of the allyl-terminated telechelic sulfone polymers using a bisazide. The sulfonated polymers in different comonomer compositions were fully characterized by H-1 NMR, and the crosslinked structure was also verified by FT-IR spectroscopic analyses. Having both the uniform distribution of the hydrophilic conductive sites and controlled hydrophobic nature by minimized crosslinking over the rigid rod poly(ether sulfone) backbone, the crosslinked polymer membrane (PES-60) offered excellent proton conductivity of 0.79 S cm(-1) at 100 degrees C together with hydrolytic and oxidative stability. In addition, only 17% of methanol permeability of the Nafion (R) was observed for the crosslinked PES-60. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: POLYMER ELECTROLYTE MEMBRANES; PROTON-EXCHANGE MEMBRANES; CONDUCTIVE POLYIMIDE ELECTROLYTES; POLY(ARYLENE ETHER); COPOLYMERS; LINKING